Determining urban‒rural coordinated development in major grain-producing areas based on urbanization and cultivated land use efficiency coordination level: A case study in Hunan Province, China - Wei, Xue; Liu, Liming; Yuan, Chengcheng; Xia, Zheyi (Frontiers in Environmental Science, 2023)
Urbanization and cultivated land use coordination is the key to urban‒rural coordinated development, especially in the major grain-producing areas in China, but it is rarely examined. A coordination framework of urbanization and cultivated land use efficiency systematically clarified how to achieve Urbanization and cultivated land use coordination. Taking Hunan Province as an example, this study explored the spatiotemporal evolution of the level of Urbanization and cultivated land use coordination from 2000 to 2018 at the county level, identified current types of Urbanization and cultivated land use coordination and discussed the key optimization measures for different types. The results showed that 1) urban‒rural coordinated development, abstractly represented by the Urbanization and cultivated land use coordination in major grain-producing areas, depends on the intensity of interactions and the level of integration of urbanization and cultivated land use systems. 2) From 2000 to 2018, the level of Urbanization and cultivated land use coordination in Hunan changed from serious maladjustment to great maladjustment to coordination. 3) The current Urbanization and cultivated land use coordination pattern in Hunan Province has a strong spatial differentiation, which can be divided into eight subregions. The key to the coordinated development of each type is to accelerate the flow of elements through deepening reform and innovation mechanisms to complement the shortcomings of development. This study will provide a scientific reference for the effective implementation of regional coordinated development strategies in major food-producing regions.